1995
DOI: 10.1111/j.1651-2227.1995.tb13520.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of complications following unintentional caustic ingestion in children. Is endoscopy always necessary?

Abstract: The records of 115 children hospitalized following caustic ingestion over an 18.5-year period from 1976 to 1994 were reviewed. The relationship between types of product ingested, signs and symptoms, degree of esophageal injury and complications was analyzed. All complications were the result of strong alkali ingestion (sensitivity = 1.0). Among the 102 incident patients, 36.8% of lye ingestions resulted in complications, whereas only 2.7% (one) of automatic dishwasher detergent (ADD) ingestions caused any comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 26 publications
7
26
2
Order By: Relevance
“…All of our patients ingested liquid substances, which would put them at higher risk of esophageal injury. In children, respiratory distress symptom is a predictor of severe digestive lesion (9,10). All but one of our subjects was adult, and we did not find this symptom.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…All of our patients ingested liquid substances, which would put them at higher risk of esophageal injury. In children, respiratory distress symptom is a predictor of severe digestive lesion (9,10). All but one of our subjects was adult, and we did not find this symptom.…”
Section: Discussioncontrasting
confidence: 46%
“…On the other hand, the routine use of endoscopic examination after corrosive ingestions is a matter of some debate (9 -12). Christesen reported that no patient with grade 0, 1, or 2a esophageal injury developed treatment-demanding complication (9). However, whether initial signs and symptoms were useful in assessing the degree of upper gastrointestinal tract injury was still contentious (5,9,10).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Chemical supraglottitis may result from ingestion or aspiration of caustic or corrosive substances [8,[11][12][13][14]. Supraglottic edema may occur as a component of allergic reactions; angioneurotic edema; adverse drug reactions, such as from angiotensin-converting enzyme inhibitors; or as a consequence of diseases such as toxic epidermal necrolysis [15].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopy is recommended if excessive drooling or dysphagia is present or if there is evidence of significant visible mucosal burns in the mouth or throat on examination. If there is doubt regarding the composition of the ingested substance or it is known to be a high-risk ingestion (as determined by pH, pK a and volume ingested), endoscopy is indicated regardless of presence/absence of these clinical indicators 9 10…”
Section: Emq Answersmentioning
confidence: 99%